2013
DOI: 10.1371/journal.pone.0071465
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Volume throughout Life: A Validated Normative Model

Abstract: The measurement of ovarian volume has been shown to be a useful indirect indicator of the ovarian reserve in women of reproductive age, in the diagnosis and management of a number of disorders of puberty and adult reproductive function, and is under investigation as a screening tool for ovarian cancer. To date there is no normative model of ovarian volume throughout life. By searching the published literature for ovarian volume in healthy females, and using our own data from multiple sources (combined n = 59,9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 41 publications
3
54
0
3
Order By: Relevance
“…According to a normative model, the ovarian volume enlargement occurs through childhood and adolescence to reach the maximum volume at 20 years of age, thereafter declining toward menopause and beyond (29). With respect to this model our nontreated volumes are close to the predicted values, and the treated volumes are substantially smaller.…”
Section: Discussionsupporting
confidence: 57%
“…According to a normative model, the ovarian volume enlargement occurs through childhood and adolescence to reach the maximum volume at 20 years of age, thereafter declining toward menopause and beyond (29). With respect to this model our nontreated volumes are close to the predicted values, and the treated volumes are substantially smaller.…”
Section: Discussionsupporting
confidence: 57%
“…At the center of this controversy is the fact that the guidelines used to define PCOM overlap with the criteria for a multifollicular ovary especially when utilizing a transabdominal approach and follicle counts. The ovarian volume starts to increase with the onset of puberty, achieves maximum volume soon after (between menarche and age 16 years), and remains stable or decreases slightly thereafter [82][83][84][85] . Follicle number and size are also noted to increase with puberty, with a higher number of small follicles during adolescence and young adulthood and a decrease thereafter [84] .…”
Section: What Are the Criteria For Pcom In Adolescents?mentioning
confidence: 99%
“…Follicle number and size are also noted to increase with puberty, with a higher number of small follicles during adolescence and young adulthood and a decrease thereafter [84] . Isolated studies have also suggested the use of MRI or Doppler examination for the diagnosis of PCOM [85][86][87][88] . Dewailly et al [79] concluded that, when using transabdominal ultrasonography, an ovarian volume >10 cm 3 should be used because follicle counts become unreliable with this methodology.…”
Section: What Are the Criteria For Pcom In Adolescents?mentioning
confidence: 99%
“…Maksymalną objętość jajniki osiągają w okresie pomiędzy menarche a 16 r.ż. [18], natomiast struktura wielopęcherzyko-wa nie zawsze świadczy o patologii. Istotny jest układ i rozmieszczenie pęcherzyków, ponieważ obecność licznych pęcherzyków ułożonych rów-nomiernie w całym jajniku nie może stanowić kryterium policystycznej morfologii jajników.…”
Section: Diagnostyka Pcos U Nastolatekunclassified